Enterprise Risk Management Berdasarkan ISO 31000 dalam Pengukuran Risiko Operasional pada Klinik Spesialis Esti - Abelia Putri Aisyah; Lely Dahlia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2022)
This research is about measuring Enterprise Risk Management based on ISO 31000:2018. This study uses a qualitative method. In this study, an analysis was carried out by identifying risks, conducting a risk assessment by measuring the risk of Probability and Impact, conducting a risk evaluation using a 3x3 matrix and handling risks. The research was conducted by direct interviews and online interviews, observation and analysis using Enterprise Risk Management. Risk identification shows that there are 10 risks to doctors and 12 risks to operational employees at the Clinic. The results of the risk measurement with a high risk value are the risk of disturbances in the computer system which should be quickly addressed by the Clinic. With ERM, it is hoped that it can help companies minimize existing or future risks and can provide an assessment of various risks.